Predicting mental health in people with multiple sclerosis through Attachment style, pain experience, and coping strategies - Doostdari, Farnaz; seifi, Ali; Arzpeyma, Mahyar; Kianimoghadam, Amir Sam (Researcher Bulletin of Medical Sciences, 2025)
Objective: This study aimed to predict mental health through Attachment style, the experience of pain, and coping strategies in MS patients of the Iranian MS association. Materials and Methods: The present study is a cross-sectional Study. It was conducted using the available Sampling method over 345 MS patients of the Iranian MS association. After obtaining informed consent, the General Health Questionnaire (GHQ-28), Short Form-McGill Pain Questionnaire-2 (SF-MPQ-2), Adult Attachment Inventory (AAI), and Coping Inventory for stressful situations short form (CISS-SF) responded. Used statistical methods, including Pearson correlation coefficient and multiple regression, were used for data analysis software were used SPSS24. Results: Mental health has a positive and significant relationship (sig=0.00 t=7.1 β=0.30) and plays a significant role in predicting mental health. Also, coping strategy (sig=0.03 t=2.1 β=0.90) and pain experience (sig=0.00 t=11.3 β=0.48) significantly predicted mental health in people with MS. Conclusion: These results suggested that mental health can predicting through attachment style, pain experience, and coping strategies.